INNOVATIVE TEACHING METHODS FOR MANAGEMENT COMPETENCIES IN INTERNATIONAL LOGISTICS (Physical Culture and Sport: Scientific Perspective, 2025)
The article highlights the trends in the modern development of logistics, characterized by rapid changes driven by globalization processes, the swift implementation of technological innovations, and the emergence of new business models. In this context, the importance of forming management competencies in future specialists is emphasized, as innovative approaches to education become key to preparing highly qualified personnel capable of effectively adapting to changing market conditions.A review of scientific research confirms the growing interest in the implementation of cutting-edge educational methods aimed at developing management skills in the field of international logistics. The current economic situation dictates the need to revise the standards of professional training to meet the current market demands. The main directions of development in this field include the application of a competence-based approach, the use of innovative technologies in the learning process, and the creation of multi-level systems of professional education.The article also examines innovative approaches in pedagogy as an update of the learning processes through the integration of modern technologies to enhance the quality of the educational process. The implementation of such methods stimulates the development of creative, analytical, and management abilities in students. Among the innovative methodologies, the use of portfolios, problem-oriented, and project-based learning stand out, which facilitate the activation of cognitive activity and the development of critical thinking.Significant attention has been paid to the integration of digital technologies into the educational process, which provides access to quality educational materials and promotes international cooperation. The use of digital platforms opens up opportunities for the implementation of individualized learning programs that meet the needs of each student. Thus, the implementation of innovative approaches and digital technologies in the training process of specialists in the field of international logistics is a determining factor for their competitiveness in the modern labor market. This contributes to the increase in the effectiveness of learning and adaptation to the demands of the global environment.
Keywords: logistics; management competencies; innovative learning methods